Current treatment landscape for obesity in Singapore - Phong Ching Lee; Chin Hong Lim; Ravishankar Asokkumar; Marvin Wei Jie Chua (Singapore Medical Journal)
The rising prevalence of obesity in Singapore is a harbinger for a corresponding increase in obesity-related complications such as type 2 diabetes mellitus (T2DM) and coronary heart disease. Obesity is a complex disease driven by multiple factors, and hence, treatment cannot follow a ‘one-size-fits-all’ approach. Lifestyle modifications involving dietary interventions, physical activity and behavioural changes remain the cornerstone of obesity management. However, similar to other chronic diseases such as T2DM and hypertension, lifestyle modifications are often insufficient on their own, hence the importance of other treatment modalities including pharmacotherapy, endoscopic bariatric therapy and metabolic–bariatric surgery. Weight loss medications currently approved in Singapore include phentermine, orlistat, liraglutide and naltrexone–bupropion. In recent years, endoscopic bariatric therapies have evolved as an effective, minimally invasive and durable therapeutic option for obesity. Metabolic–bariatric surgery remains the most effective and durable treatment for patients with severe obesity, with an average weight loss of 25%–30% after one year.